Genetics of CFTR and male infertility - Bieniek, Jared M. (Transl Androl Urol, 2021)
Cystic fibrosis (CF) is a rare autosomal-recessive disorder manifested as multisystem organ dysfunction. The cystic fibrosis transmembrane conductance regulator (CFTR) protein functions as an ion transporter on the epithelium of exocrine glands, regulating secretion viscosity. The CFTR gene, encoded on chromosome 7, is required for the production and trafficking of the intact and functional CFTR protein. Literally thousands of human CFTR allelic mutations have been identified, each with varying impact on protein quality and quantity. As a result, individuals harboring CFTR mutations present with a spectrum of symptoms ranging from CF to normal phenotypes. Those with loss of function but without full CF may present with CFTR-related disorders (CFTR-RDs) including male infertility, sinusitis, pancreatitis, atypical asthma and bronchitis. Studies have demonstrated associations between higher rates of CFTR mutations and oligospermia, epididymal obstruction, congenital bilateral absence of the vas deferens (CBAVD), and idiopathic ejaculatory duct obstruction (EDO). Genetic variants are detected in over three-quarters of men with CBAVD, the reproductive abnormality most classically associated with CFTR aberrations. Likewise, nearly all men with clinical CF will have CBAVD. Current guidelines from multiple groups recommend CFTR screening in all men with clinical CF or CBAVD though a consensus on the minimum number of variants for which to test is lacking. CFTR testing is not recommended as routine screening for men with other categories of infertility. While available CFTR panels include 30 to 96 of the most common variants, complete gene sequencing should be considered if there is a high index of suspicion in a high-risk couple (e.g., partner is CFTR mutation carrier). CF treatments to date have largely targeted end-organ complications. Novel CFTR-modulator treatments aim to directly target CFTR protein dysfunction, effectively circumventing downstream complications, and possibly preventing symptoms like vasal atresia at a young age. Future gene therapies may also hold promise in preventing or reversing genetic changes that lead to CF and CFTR-RD.